The Effect of Problem-Based Learning Model with Realistic Mathematics Education Approach on Mathematical Communication Skills - Suharti; Nur Fakhriyah Syahid; Baharuddin; Lisnasari Andi Mattoliang; Nurmala R (Proceeding of International Conference on Multidisciplinary Research, 2024)
This research aims to determine the effect of the Problem-Based Learning (PBL) model with the Realistic Mathematics Education (RME) approach on students' mathematical communication skills. This research approach uses a quantitative approach with an experimental research type, a quasi-experimental type with a pretest-posttest control design. The population in this study was 107 MTs Guppi Buntu Barana students. The research sample consisted of 36 students. The sampling technique uses Cluster Random Sampling. Tests and observations were carried out for data collection. The research instruments used in this research were mathematical communication ability test questions and observation sheets. Data analysis techniques use descriptive statistical analysis and inferential statistical analysis. The results of this research show that the average mathematical communication ability of students in classes that do not use the PBL model with the RME approach from pretest to post-test increased from 34.50 to 81.56, with an increase of 47.06. The mathematical communication skills of students in classes that use the PBL model with the RME approach obtained an average score from pretest to posttest that increased from 40.39 to 89.72, with an increase of 49.33. So, the PBL model with the RME approach has a significant influence on students' mathematical communication skills.